SECOND LINE DRUG THERAPY IN PATIENTS WITH RHEUMATOID ARTHRITIS - Lale Yılmaz,; Güney Aslan,; Hatice Bodur, (Archives of Rheumatology, 2003)
The aim of this study is to evaluate the impact of the second line drugs in patients with rheumatoid arthritis (RA). The analysis covered 117 female and 23 male with a total of 140 patients at the mean age of 50,71±13,49. The treatment monitored and analyzed retrospectively by anamnesis and by evaluating the records of the patients. In this study, the side effects necessitating discontinuation of the drug therapy were also examined. The most commonly used drug (58,2 percent 82 patients) was methotrexate (MTX). In total, the number of patients who halted using the drug because of its side effect was minimum (8,53 percent) in MTX users. The number was the highest (31,14) in the sulfasalazine (SSZ) users. The most common side effect (14,75 percent) was in the gastrointestinal system. The rate of discontinuation of the SSZ because of its ineffectiveness was determined as 14,75 percent. The rate of discontinuation of the drug due to ineffectiveness was the highest in the antimalarial therapy which was 23,8 percent for Hydroxychloroquine (HCQ) and 15,75 percent for Choloroquine (CL). Discontinuation due to its side effects was relatively low with antimalarial drugs. Retinopathy (1,74%), GIS side effects (3,5%), rash (1,74%), ototoxicity (1,74%) was observed in patients treated with CL, and 9,52 % of patients had ototoxic side effects in treatment with HCQ. No fatal and severe drug reactions were observed in any of the patients. In our results efficacy, toxicity and security profile were in accordance with the literature. MTX has higher efficacy and lower toxicity. Although antimalarial drugs are not the most effective drugs, they are relatively secure. These drugs preserve their importance, as the treatment and follow up are not so expensive. This study emphasizes the importance of careful monitorization of RA patients on second line drug treatment in order to recognize side effects.